THE STUDY ANALYSIS OF IRON DEFICIENCY ANEMIA FOR FEMALE STUDENTS OF STATE SENIOR HIGH SCHOOL - Permatasari, Putri; Priliantini, Anjang; Rizkia Anjani, Sheila (Malaysian Journal of Public Health Medicine, 2021)
Iron deficiency anaemia in adolescents is one of the public health problems that has not been overcome especially in young women. One of the indirect causes is income, parental education, and low knowledge about anaemia and balanced nutrition. Quantitative design with descriptive study supported with qualitative design. Samples were female students of State Senior High Senior (n=394). Data were collected using a questionnaire. Anaemia prevalence was 46.4%, with classifications on the severe level at 8.6%, moderate level at 20.1%, and mild level at 17.8%. Respondents' knowledge about anaemia was pretty good (67.3%), balanced nutrition (51.3%). The observation showed that the foods in the cafeteria were not varied, unhealthy, not nutritious, and unhygienic. Personal hygiene and food sanitation were low. There were no regulations and no changing menu schedules. Peer group takes a role in selecting foods. Balanced nutrition food had not been well-socialized. Knowledge of anaemia, balanced nutrition, which is quite high, do not reduce the prevalence of anaemia in adolescent. It is needed to take interventions to prevent and overcome iron deficiency anaemia with a holistic communication network among students, school authorities, and cafeteria management.